Salafi-Jihadist Movements and Ideology in Educational Institutions: Exploring the Nexus with Religious Moderation - Hatim Gazali; Dewi Anggraeni; Mariam Eit Ahmed (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The global proliferation of Salafi-Jihadist movements has raised serious concerns about ideological infiltration into educational institutions, particularly in predominantly Muslim countries like Indonesia. This study aims to explore how Salafi-Jihadist ideology manifests within Islamic educational institutions and how such influence interacts with state-promoted religious moderation programs. Positioned within a critical historical framework, this research employs a qualitative design that integrates content analysis of scholarly literature and actor based inquiry to map the ideological characteristics of Salafi-Jihadism and the institutional responses to its spread. The findings highlight three key insights: first, Salafi-Jihadist movements present a doctrinally rigid and exclusionary interpretation of Islam that challenges inclusive religious practices; second, the ideological appeal of Salafi-Jihadism lies in its claim to scriptural authenticity and puritanical simplicity, making it attractive to specific youth cohorts; and third, religious moderation initiatives—particularly through curriculum reform, institutional policy, and cultural engagement—serve as effective counter-strategies to mitigate radical influences. These findings offer important implications for policymakers, educators, and religious leaders, emphasizing the urgency of developing preventive frameworks that integrate theological inclusivity and critical pedagogy. Ultimately, the study contributes to a deeper understanding of the ideological contestations within Islamic education and proposes grounded strategies to safeguard religious institutions from extremism